2015
DOI: 10.1038/ki.2014.423
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of eculizumab in atypical hemolytic uremic syndrome from 2-year extensions of phase 2 studies

Abstract: Atypical hemolytic uremic syndrome (aHUS) is a rare, possibly life-threatening disease characterized by platelet activation, hemolysis and thrombotic microangiopathy (TMA) leading to renal and other end-organ damage. We originally conducted two phase 2 studies (26 weeks and 1 year) evaluating eculizumab, a terminal complement inhibitor, in patients with progressing TMA (trial 1) and those with long duration of aHUS and chronic kidney disease (trial 2). The current analysis assessed outcomes after 2 years (medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
325
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(358 citation statements)
references
References 40 publications
25
325
0
8
Order By: Relevance
“…This finding might be a reason of the LDH normalization in less than 60% patients in this study especially under the diverse patient characteristics mentioned above, which could lead to the reduced achievement of complete TMA response. Prior studies suggest that eculizumab is well tolerated [10,11]. In this study, each of the ARs was reported in very few patients, although some reactions were classified as serious.…”
Section: Discussionmentioning
confidence: 81%
“…This finding might be a reason of the LDH normalization in less than 60% patients in this study especially under the diverse patient characteristics mentioned above, which could lead to the reduced achievement of complete TMA response. Prior studies suggest that eculizumab is well tolerated [10,11]. In this study, each of the ARs was reported in very few patients, although some reactions were classified as serious.…”
Section: Discussionmentioning
confidence: 81%
“…Of note, these data come from the historical studies treated with plasma therapy [14,23,24]. Recent advances of therapy including early initiation of plasma therapy or eculizumab administration significantly improved the mortality and prognosis of aHUS [62,68]. In the near future, the data showing prognosis of aHUS patients depending on the genetic background treated with eculizumab will be clarified.…”
Section: Prognosismentioning
confidence: 99%
“…Decreased platelet counts observed in patients with aHUS usually resolve after 1 to 2 weeks of eculizumab therapy [41][42][43].…”
Section: Treatments Therapeutic Considerationsmentioning
confidence: 99%